Exploring the Relationship Between Instagram Usage, Self-Identity and Friendship Quality - Osude, Oluwaleke Micheal (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The study explores the impacts of Instagram usage on self-identity and friendship quality. Instagram is widely domiciled among young adults. Instagram users may likewise follow others on the stage without their endorsement and this may improve the social networks for the individuals who have restricted social ties outside of the application. The study means to know the association between digital media, society, and personality development is considering in online media use. For this purpose, Instagram usage investigated to find out kinship quality and the relationship with a social personality. The research adopted a quantitative survey method through the use of Google form to sample 400 young Nigerian Instagram users living in North Cyprus. Results therefore revealed that frequent use of Instagram has positive influence on the friendship quality of the respondents. It was also uncovered that recurrence of Instagram use has an important relationship on the self- personality of the respondents (r = .28). Keywords: Self-identity, Friendship quality, Social Networking Sites, Instagram, Online friendshi

ÖZ: Bu çalışma, Instagram kullanımının öz kimlik ve arkadaşlık kalitesi üzerindeki etkilerini araştırmaktadır. Instagram, genç yetişkinler arasında yaygın bir şekilde kullanılmaktadır. Instagram kullanıcıları, başka kişilerin onayı olmadan onları takip edebilmektedir ve bu durum, sosyal ağ kullanımı zayıf olan bireylerin sosyal bağlarını geliştirebilmektedir. Çalışma, dijital medya, toplum ve kişilik gelişimi ile çevrimiçi medya kullanımı arasındaki ilişkiyi araştırmaktadır. Ayrıca, Instagram kullanımının, çevrimiçi akrabalık ilişkisi, sosyal ve kişisel ilişkiler gibi çevrimiçi iletişim ile nasıl geliştiğini ortaya koymaya çalışmaktadır. Araştırmanın kapsamının örneklemeni oluşturan Kuzey Kıbrıs’ta yaşayan 400 genç Nijeryalı Instagram kullanıcısı ile Google form kullanılarak anket çalışması benimsenmiştir ve nicel bir çalışma gerçekleştirilmiştir. Çalışmanın sonucunda Instagram’ın sık bir şekilde kullanılmasının, arkadaşlık kalitesi üzerine manidar bir etkisi olduğu görülmüştür. Bununla birlikte Instagram kullanımı ve kişilik arasında anlamlı bir ilişki olduğu belirlenmiştir(r = .28). Anahtar Kelimeler: Öz kimlik, Arkadaşlık kalitesi, Sosyal Ağ Siteleri, Instagram, Çevrimiçi arkadaşlık
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2021. Supervisor: Assoc. Prof. Dr. Aysu Arsoy.
Keywords: Communication and Media Studies; Social Media -Social Networking Sites-Interpersonal Communication-Friendship; Instagram-Self Identity-Friendship; Online social networks - Communication; Social media-Psychological aspects; Social media and society; Self-identity; Friendship quality; Social Networking Sites; Instagram; Online friendship